2016
DOI: 10.1016/j.bbamem.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transmembrane helix 1 (TM1) surfaces important for EnvZ dimerisation and signal output

Abstract: The Escherichia coli sensor kinase EnvZ modulates porin expression in response to various stimuli, including extracellular osmolarity, the presence of procaine and interaction with an accessory protein, MzrA. Two major outer membrane porins, OmpF and OmpC, act as passive diffusion-limited pores that allow compounds, including certain classes of antibiotics such as β-lactams and fluoroquinolones, to enter the bacterial cell. Even though the mechanisms by which EnvZ detects and processes the presence of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…This argues against large displacement of the two helices relative to one another in response to modulation. Interestingly, similar results have been reported for the sensor kinases DcuS and EnvZ (34,35). Those authors have instead proposed a symmetrical piston movement of the TM helices to transduce the signal.…”
Section: Resultssupporting
confidence: 67%
“…This argues against large displacement of the two helices relative to one another in response to modulation. Interestingly, similar results have been reported for the sensor kinases DcuS and EnvZ (34,35). Those authors have instead proposed a symmetrical piston movement of the TM helices to transduce the signal.…”
Section: Resultssupporting
confidence: 67%
“…4). It should be noted that this significant difference at the periplasmic end of the TMD between cells grown under the low‐ and high‐osmolarity regime was not observed during similar analyses of TM1 (25).…”
Section: Resultsmentioning
confidence: 80%
“…We previously found that the Cys-less version of EnvZ had similar steady-state signal output and response to environmental osmolarity as the wild-type version of EnvZ making it suitable for comparisons of in vivo sulfhydryl-reactivity and signal output analysis. We initially determined that no major rearrangements occur along the TM1-TM1’ interface upon stimulus perception (25). As minimal change was observed along this helical interface in response to osmolarity, we continued by examining the TM2-TM2’ interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of residues previously assessed to contain TM1 was described in [28]. Briefly, the primary sequence of EnvZ from Escherichia coli K-12 MG1655 (NP_417863.1) was subjected to a full protein scan with DGpred, which calculates the ΔG app for transmembrane insertion throughout the entire length of the submitted sequence [29].…”
Section: Selection Of Residues For Assessmentmentioning
confidence: 99%